The Role Of The Village Head In Earth And Building Tax Withdrawal In Papahan Village, Tasikmadu District, Karanganyar Regency During The Covid-19 Pandemic - Widayanti; Agus Widodo (International Journal of Educational Research & Social Sciences, 2022)
Land and Building Tax is one of the sources of financing for regional development and other sources. In urban and rural areas, the intensification and extensification of land and building tax collection will increase state revenues. Land and Building Tax receipts will be submitted to the Regency/Municipal and Village Governments using a percentage system. Tax sanctions impact the provisions of laws that have been given are disobeyed. The greater the error made, the taxpayer will be subject to severe sanctions if the taxpayer does not carry out his obligations, namely by paying taxes. This study uses a normative juridical approach to qualitative legal research by analyzing library materials or secondary data. This study draws conclusions derived from interpreting laws relevant to the topics discussed. In addition, this study also analyzes the legal principles used to formulate research objectives. The strategies used in optimizing tax collections include evaluating taxpayers to analyze names that are not always punctual in paying taxes taking firmness in the form of warnings to taxpayers who do not pay taxes. Several sanctions have been attached, conducting regular and periodic counseling to taxpayers who are expected to provide insight into the timeliness of paying taxes. They have quality resources to assist in data input and updating in an integrated system.